Diet‐Induced Dysbiosis and Genetic Background Synergize With Cystic Fibrosis Transmembrane Conductance Regulator Deficiency to Promote Cholangiopathy in Mice. Issue 12 (10th October 2018) - Debray, Dominique; El Mourabit, Haquima; Merabtene, Fatiha; Brot, Loïc; Ulveling, Damien; Chrétien, Yves; Rainteau, Dominique; Moszer, Ivan; Wendum, Dominique; Sokol, Harry; Housset, Chantal
Abstract : The most typical expression of cystic fibrosis (CF)–related liver disease is a cholangiopathy that can progress to cirrhosis. We aimed to determine the potential impact of environmental and genetic factors on the development of CF‐related cholangiopathy in mice. Cystic fibrosis transmembrane conductance regulator ( Cftr ) −/− mice and Cftr +/+ littermates in a congenic C57BL/6J background were fed a high medium‐chain triglyceride (MCT) diet. Liver histopathology, fecal microbiota, intestinal inflammation and barrier function, bile acid homeostasis, and liver transcriptome were analyzed in 3‐month‐old males. Subsequently, MCT diet was changed for chow with polyethylene glycol (PEG) and the genetic background for a mixed C57BL/6J;129/Ola background (resulting from three backcrosses), to test their effect on phenotype. C57BL/6J Cftr −/− mice on an MCT diet developed cholangiopathy features that were associated with dysbiosis, primarily Escherichia coli enrichment, and low‐grade intestinal inflammation. Compared with Cftr +/+ littermates, they displayed increased intestinal permeability and a lack of secondary bile acids together with a low expression of ileal bile acid transporters. Dietary‐induced (chow with PEG) changes in gut microbiota composition largely prevented the development of cholangiopathy in Cftr −/− mice. Regardless of Cftr status, mice in a mixed C57BL/6J;129/Ola background developed fatty liver under an MCT diet. The Cftr −/− mice in the mixed background showed no cholangiopathy, which was not explained by a difference in gut microbiota or intestinal permeability, compared with congenic mice. Transcriptomic analysis of the liver revealed differential expression, notably of immune‐related genes, in mice of the congenic versus mixed background. In conclusion, our findings suggest that CFTR deficiency causes abnormal intestinal permeability, which, combined with diet‐induced dysbiosis and immune‐related genetic susceptibility, promotes CF‐related cholangiopathy.